An introduction to film and TV production : from concept to market - Richie, Joseph; Russell, Karen; Vincent, Airielle; Winston, Tameka (New York. NY : Routledge, 2022)
"This streamlined, step-by-step guide provides students and newcomers in the field of media with an overview of the complete production process, from conceiving of an idea to marketing the final product. Readers will learn what it takes to create a concept, develop it, and then market and sell it. Chapters discuss pitching, producing, marketing visionary concepts, financing, and distributing content. Focused on traditional and non-traditional platforms including social media, websites, and online advertising, this book explores currently evolving media platforms, ideas, and practices and provides examples of how to navigate these unique creative processes. Interviews with business executives offer insider tips and tricks to creating a marketable project. In this book, you will learn how to: Distinguish between a "great idea" and a "marketable idea." Condense your concept into an effective "elevator pitch." Build a basic business plan. Create a marketing strategy, be it traditional, digital, or both. Establish a personal brand and portfolio that will grab the right attention. And more! This book will be of great help to the student, independent filmmaker, and content creator looking to understand the process of getting their work produced, distributed, and marketed"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Motion pictures -- Production and direction; Television -- Production and direction; Digital media -- Production and direction; Motion pictures -- Marketing; Television programs -- Marketing; Digital media -- Marketing